2016
DOI: 10.1038/aps.2015.123
|View full text |Cite
|
Sign up to set email alerts
|

Eukaryotic elongation factor 2 kinase as a drug target in cancer, and in cardiovascular and neurodegenerative diseases

Abstract: Eukaryotic elongation factor 2 kinase (eEF2K) is an unusual protein kinase that regulates the elongation stage of protein synthesis by phosphorylating and inhibiting its only known substrate, eEF2. Elongation is a highly energy-consuming process, and eEF2K activity is tightly regulated by several signaling pathways. Regulating translation elongation can modulate the cellular energy demand and may also control the expression of specific proteins. Growing evidence links eEF2K to a range of human diseases, includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
86
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(88 citation statements)
references
References 65 publications
1
86
0
Order By: Relevance
“…Similar findings have also been reported for the human IUGR placenta (12,74). The role of eEF2K in adapting cell growth to nutrient deprivation has gotten considerable attention recently as an approach to treating cancer (49,68). Some forms of cancer cells appear to adapt to their nutrient-limiting environment by inhibiting eEF2K activity at the posttranslational level (18,70).…”
Section: Discussionsupporting
confidence: 75%
“…Similar findings have also been reported for the human IUGR placenta (12,74). The role of eEF2K in adapting cell growth to nutrient deprivation has gotten considerable attention recently as an approach to treating cancer (49,68). Some forms of cancer cells appear to adapt to their nutrient-limiting environment by inhibiting eEF2K activity at the posttranslational level (18,70).…”
Section: Discussionsupporting
confidence: 75%
“…In this study, we show that eEF2K activating pathways such as mTORC1 inhibition, AMPK, or the ISR were not involved in NFR-mediated eEF2K activation. Possible alternative pathway that could contribute to NFR-mediated effects includes calcium ion influx, hypoxia, or ERK signaling, which have been proposed to regulate eEF2K [44]. It ◀ Figure 5.…”
Section: Discussionmentioning
confidence: 99%
“…eEF2K is a Ca2ĂŸ/ calmodulin-dependent serine/threonine kinase important for the regulation of elongation of protein translation (Monteggia et al, 2013). Elongation is a highly energy-consuming process, and eEF2K activity is tightly regulated by several signaling pathways (Liu and Proud, 2016). eEF2K is expressed in neurons, and recent evidence suggests that it may play a role in processes such as learning and memory and in depression (Liu and Proud, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Elongation is a highly energy-consuming process, and eEF2K activity is tightly regulated by several signaling pathways (Liu and Proud, 2016). eEF2K is expressed in neurons, and recent evidence suggests that it may play a role in processes such as learning and memory and in depression (Liu and Proud, 2016). In fact, Park et al (2008) showed that eEF2K plays an important role in the synthesis of Arc/Arg3.1, a protein involved in neurotransmitter receptor trafficking and in long-term depression, a process that reflects changes in synaptic strength.…”
Section: Discussionmentioning
confidence: 99%